Investigations on the influence of composition in the development of Ni–Ti shape memory alloy using laser based additive manufacturing. (June 2015) - Shiva, S.; Palani, I.A.; Mishra, S.K.; Paul, C.P.; Kukreja, L.M.
Abstract: Among the various shaped memory alloys (SMA), nitinol (Ni–Ti alloy) finds applications in automotive, aerospace, biomedical and robotics. The conventional route of fabrication of SMA has several limitations, like formation of stable secondary phases, fabrication of simple geometries, etc. This paper reports a novel method of fabricating SMA using a laser based additive manufacturing technique. Three different compositions of Ni and Ti powders (Ni-45% Ti-55%; Ni-50% Ti-50%; Ni-55% Ti45%) were pre-mixed using ball-milling and laser based additive manufacturing system was employed to fabricate circular rings. The material properties of fabricated rings were evaluated using Scanning Electron Microscopy (SEM), Differential scanning calorimeter (DSC), X-ray diffraction (XRD) system and micro-hardness test. All the characterized results showed that SMA could be manufactured using the laser based additive manufacturing process. The properties of laser additive manufactured SMA (Ni-50% Ti-50%) were found to be close to that of conventionally processed SMA. Highlights: A novel method of SMA fabrication is explored. Microhardness was good for the samples. XRD results shown, supported by DSC observations. Fabricated SMA is at par with conventional SMA.